Acute Phase Proteins and Procalcitonin in the Modeling of Infectious Arthritis - Mahomedov, S.; Poliachenko, Yu.V.; Hrytsai, M.P.; Litovka, I.H. (TERRA ORTHOPAEDICA, 2022)
Background. Acute phase proteins – ceruloplasmin, haptoglobin, C-reactive protein (CRP) – are markers that characterize the inflammatory process. C-reactive protein is one of the major components of the acute phase (AF) and is a generally accepted indicator of inflammatory processes. Objective: to determine the level and specificity of acute-phase proteins (CRP, haptoglobin, ceruloplasmin), as well as procalcitonin in the modeling of infectious arthritis. Materials and Methods. Experimental studies were carried out on 31 white male Wistar rats. The model of infectious arthritis was created during three days by daily injection of 0.02 ml of S.aureus 108 No. 209 into the knee joint of a rat. The animals were divided into groups, of which group I was the vivarium control. The following model of drug administration was used for the experimental groups: a single daily injection of 0.02 ml of flosteron into the knee joint for three days (group II); daily single administration for three days of 0.02 ml of S.aureus 108 No. 209 (group III); daily one-time alternating (every other day) administration for three days of 0.02 ml of flosteron and 0.02 ml of S.aureus 108 No. 209 into the knee joint (group IV). The effectiveness of the drugs was observed 3 and 14 days after administration. Results. It was established that the concentration of haptoglobin probably increased in the blood serum of rats after 3 days only under the conditions of alternating three-time administration of flosterone and S.aureus 108 No. 209. After 14 days, when the inflammatory progress progressed, this indicator increased in all studied groups of animals, and most of all (by analogy with observations after three days) with the combined effect of flosterone and S.aureus 108 No. 209. The concentration of ceruloplasmin in blood serum increased in all experimental rats both after 3 days and after 14 days in the group after administration of flosterone. The content of C-reactive protein in blood serum increased in all studied groups of rats without exception, which proves its high specificity for detecting inflammatory processes of various severity. The concentration of procalcitonin in the experiment did not reliably change in the blood serum of rats of any experimental group after 3 days. However, significant changes occurred 14 days after the introduction of flosterone and with the combined effect of flosterone and S.aureus 108 No. 209. Conclusions. Determining the content of haptoglobin is not highly effective in early detection of the inflammatory process. At the same time, the synthesis of ceruloplasmin increases precisely during the first three days of the infectious process, which turns it into an effective marker for detecting early infectious complications. The dynamics of changes in the level of C-reactive protein in blood serum demonstrated the highest correlation with the activity of the infectious process, which proves its high specificity for detecting inflammatory processes of various severity. The greatest deviations were observed in rats, which were injected three times alternately (every other day) with flosterone and S. aureus 108 No. 209 into the knee joint. Such changes suggest that the hormonal drug flosteron contributed to the intensification of the inflammatory process.